Regional spread pattern predicts survival in patients with sporadic amyotrophic lateral sclerosis - Gargiulo Monachelli, Gisella Mariana (2012)
Background and purpose: Sporadic amyotrophic lateral sclerosis (sALS) is a disease with a focal clinical onset and contiguous spread. We examined patterns of disease spread following symptoms onset in sALS and whether the pattern of spread predicted survival. Methods: Review of medical records (2003-2009) at London Ontario and Buenos Aires clinic cohorts retrieved 318 patients with sporadic sALS. According to patient self-report, we determined eight spread patterns: rostro-caudal, caudo-rostral, crossed, circular, superior interposed, middle interposed, inferior interposed and isolated. The variables studied were as follows: age, gender, sALS phenotypes, time from onset to diagnosis and time and direction of the spreading to the first region. Survival from symptoms onset was analysed by Kaplan-Meier, Tarone-Ware and Cox proportional hazards methods. Results: The direction of first spread was horizontal in 33%, rostral to caudal in 32% and caudal to rostral in 21%, whereas spread to remote regions was observed in 14% of patients. Survival curves and 3- and 5-year survival rates favoured patients with an isolated and caudo-rostral pattern of spread compared to patients progressing to distant regions without involvement in the intervening region, or 'superior and inferior interposed patterns' (Tarone-Ware P=0.001, χ2=0.002 and χ2=0.006, respectively). Factors affecting survival were gender, time to diagnosis, flail arm phenotype and age at diagnosis. Conclusions: We have provided evidence that not all spread in ALS is contiguous and that the nature of symptom progression influences survival. Patients with sALS with 'interposed patterns' had a worse prognosis, whereas patients with caudo-rostral pattern fared better than the rest. © 2012 The Author(s). European Journal of Neurology © 2012 EFNS.